Determinasi Adopsi Inovasi dan Dampaknya terhadap Produktivitas Usahatani Jagung - Sofya A. Rasyid; Haeruddin; Endah Wahyuning Asih (Perum BULOG, 2026)
Background: Maize farming productivity in rural areas still faces several challenges, particularly the low adoption of agricultural innovations, limited effectiveness of extension services, and the suboptimal role of farmer groups. For smallholder farmers, understanding the factors that encourage the adoption of innovations is essential to improve production outcomes. Objectives: This study aims to analyze the factors influencing the adoption of agricultural innovations and their impact on maize farming productivity in Bobo Village, Palolo District, Sigi Regency.Methods: This study employs a quantitative approach using primary and secondary data obtained through a survey of 100 corn farmers. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the variables: access to extension services, participation in farmers’ groups, ease of innovation, adoption rate, and productivity. Results and Discussion: The results show that is not sufficient by only providing information or technology, but must be followed by the actual adoption of innovations by farmers. The adoption of innovations acts as a key link between extension services, ease of technology, and farmer group participation with production outcomes. Conclusion: This study highlights the importance of improving the quality of extension services, strengthening farmer groups, and providing innovations that are easy to implement, in order to support sustainable increases in agricultural productivity.